Implementation of Independent Learning-Independent Campus at the Department Level of Islamic Religious Higher Education - Khaeroni Khaeroni; Sabri Sabri (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2022)
This study describes the implementation of an independent learning-free campus and the obstacles encountered in implementing an independent learning-free campus at the department level. The research approach used is qualitative. Data collection techniques include observation, interviews, and documentation. The data obtained from the research results were processed using qualitative descriptive data analysis. Implementing an independent learning-free campus at the department level begins with redesigning the curriculum and following the basic principles of an independent learning-independent campus. However, there are obstacles to implementing the independent study-free campus policy at the department level. First, the understanding of independent learning-an independent campus among lecturers and staff still needs to be cohesive and comprehensive. Second, the department needs to readjust the curriculum involving multiple stakeholders. Third, the availability of human resources. Fourth, the need for apprentice and entrepreneurial partners. Fifth, there is no particular unit that handles independent learning-independence campuses. Sixth, the learning process is less interactive. Lastly, socialization still needs to be carried out massively, especially in departments. Recommendations for these findings can be used as a basis for policymakers in implementing an independent learning-free campus.